2009
DOI: 10.2169/internalmedicine.48.1748
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Investigation of Inflammatory Bowel Disease in China

Abstract: The study by Bai et al (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…As China has undergone rapid industrialization over the past few decades, changes such as Western dietary habits and a more sedentary lifestyle have become the norm; as a result, it has been reported that the incidence and prevalence of IBD in provinces and cities in mainland China is increasing. [17][18][19] It should be noted that, according to Chinese literature and our experience, there are fewer extraintestinal manifestations and complications, and fewer fistulous and perianal complications, but LGIB is a relatively common manifestations for Chinese IBD patients. 20 However, the present study also had some limitations.…”
Section: Discussionmentioning
confidence: 75%
“…As China has undergone rapid industrialization over the past few decades, changes such as Western dietary habits and a more sedentary lifestyle have become the norm; as a result, it has been reported that the incidence and prevalence of IBD in provinces and cities in mainland China is increasing. [17][18][19] It should be noted that, according to Chinese literature and our experience, there are fewer extraintestinal manifestations and complications, and fewer fistulous and perianal complications, but LGIB is a relatively common manifestations for Chinese IBD patients. 20 However, the present study also had some limitations.…”
Section: Discussionmentioning
confidence: 75%